The safety of early pregnancy exposure to granisetron. (February 2020) - Shapira, Moran; Avrahami, Inbal; Mazaki-Tovi, Shali; Shai, Daniel; Zemet, Roni; Barzilay, Eran
Abstract: Objective: Current guidelines suggest that granisetron is an optional treatment for nausea and vomiting in pregnancy (NVP) despite lack of evidence to support fetal safety. We aimed to determine the association between early pregnancy exposure to granisetron and fetal/neonatal outcomes. Design: Medical records of patients treated for NVP during the first and second trimester between June 2013 to September 2015 were reviewed. Patients were asked to participate in the study by answering a detailed questionnaire regarding newborn's health and complementary data. Pregnancy outcomes of patients exposed to granisetron were compared with those of patients who were not exposed to granisetron. Results: 100 Granisetron exposed pregnancies were compared with 108 granisetron unexposed pregnancies. Exposure to granisetron occurred in the first trimester in 88 patients (94 fetuses). Maternal characteristics, history of anomalies in first degree relatives, co-exposure to other substances and extent of prenatal sonographic surveillance were comparable between both groups. Miscarriage rate was significantly lower among granisetron exposed patients compared to controls (0 vs 5.5 %, respectively, p = 0.03). Three major malformations were identified prenatally or postnatally in each of the groups (2.77 % Vs 2.83 %, p = 1). The rate of major malformations was similar between exposed and unexposed fetuses even after excluding second trimester exposure (3.2 % vs. 2.83 %, respectively p = 1). Mean gestational age at delivery, mean newborn weight and incidence of small for gestation age, were not significantly different between the groups. Conclusion: Granisetron exposure was not associated with increased risk for minor or major fetal anomalies. This study provides preliminary reassurance regarding the safety of in-utero exposure to granisetron.